Factors influencing self-control in older patients with atrial fibrillation following radiofrequency catheter ablation: a cross-sectional study based on triadic reciprocal determinism - Ding Yunmei; Zhang Yuan; Zhao Xiaojing; Liu Jialin; Zhang Yanyan; Yue Shouwei (BMC Geriatrics)
Abstract Background Atrial fibrillation (AF) has become increasingly prevalent among the older Chinese population. Radiofrequency catheter ablation (RFCA) represents an efficient procedure to reduce and minimize deleterious consequences in older patients with AF. However, self-control is often impaired in older patients, potentially affecting their recovery following surgical treatments—which can result in repeated episodes of both AF and hospital readmission. This cross-sectional study aimed to investigate self-control among older patients with AF following RFCA procedures and identify the factors that influence it, with the goal of gaining insights to inform the development of relevant clinical metrics for healthcare practitioners. Methods Between May and November 2024, we conducted an investigation among older patients aged ≥ 60 years with AF who were follow-up with in hospital over the first month after having received RFCA treatment. A variety of questionnaires were used, including the General Information Questionnaire; as well as Chinese version of the Brief Self-Control Scale, Perceived Social Support Scale, Family APGAR Index, and Hospital Anxiety and Depression Scale. Univariate, correlation, and multiple linear regression analyses were used to investigate the factors influencing self-control in older patients with AF. Results A total of 230 questionnaires were distributed and 217 valid ones were returned, yielding a valid return rate of 94.35%. The total score for self-control was 22.48 ± 6.28, representing a moderate level. The multiple linear regression analyses revealed that the most important factors that negatively influenced self-control among our cohort of older patients were EHRA symptom classification and anxiety and depression, while family care and social support positively promoted better self-control. Conclusion Self-control among older Chinese patients with AF after RFCA is currently insufficient and should be improved. Healthcare practitioners should consider intervening to reduce anxiety and depression, as well as promote social support and family care among their patients to improve self-control, prognosis, and quality of life from both individual and environmental perspectives. Trial registration Not available.